Analisis Perbandingan Metode Rasional dan Nakayasu untuk Penentuan Kapasitas Sump Pit 19AS - Nadia Rahmavidy Gitarista; Tedy Agung Cahyadi; Reza Ferdyan; Edward Pernando (Mataram University, 2026)
A well-designed drainage system is a fundamental component in planning new open-pit (greenfield) mining operations to ensure production continuity and operational safety from the outset. This study aims to compare the Rational and Nakayasu methods in a hydrological analysis to design the sump capacity of Pit 19AS, with a catchment area of 289 ha. The methodology includes rainfall frequency distribution analysis, runoff discharge estimation using both methods, and water balance simulation to determine sump capacity. The results show significant differences between the two approaches. The Rational method produces a static runoff estimate due to the assumption of uniform rainfall intensity, resulting in a sump volume of 168,773 m³. In contrast, the Nakayasu method more effectively represents flow dynamics by incorporating lag time and recession phases in the hydrograph, yielding a sump volume of 179,156 m³. Based on the water balance simulation, the Nakayasu method is recommended as a more reliable and representative approach for sump design in greenfield open-pit mining, particularly for large catchment areas such as the 289 ha case, as it complies with the mine drainage feasibility standards outlined in the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018.